Remaining Service Life Discharge Conveyor F pada Tambang Batubara PT XYZ di Kabupaten Banjar, Provinsi Kalimantan Selatan - Rahma Azizah Kotta; Elfida Moralista; Noor Fauzi Isniarno (UNISBA Press, 2023)
Abstract. Conveyor is a means of conveyance used in the mining industry to move mining materials. The conveyor structure is made of steel which is prone to corrosion as a result of environmental influences which can cause a reduction in thickness and reduce the remaining life of the conveyor structure. This research was conducted to determine the type of corrosion, corrosion control method, corrosion rate, and the Remaining Service Life of the conveyor structure. The methodology used in this research is thickness reduction measurement. The conveyor structure has a length of 96 meters consisting of 3 segments with 25 test points. Measurements were made using a Smart Sensor Ultrasonic Thickness Gauge TT 130. The output obtained is the reduced thickness value which is used to determine the Corrosion Rate and Remaining Service Life. The environmental conditions of the study area in 2015-2020 had an average rainfall of 218.32 mm/year, an average relay humidity of 81.37% and an average temperature 25.92 0C. The type of corrosion that occurs in the conveyor structure is uniform corrosion. The corrosion control method used is the coating method with a three layers system. Coating method for primary coating using Seaguard 5000, Intermediate coating using Sherglass FF, and top coating using allphatic acrylic modified polyurethane. The corrosion rate of the conveyor structure ranges from 0.18 - 0.31 mm/year and based on the relative corrosion resistance of steel it is included in the good category. The service life of the conveyor structure is 7 years and the remaining service life ranges from 6.53 - 9.49 years, so there are 11 test points or 44% test points which are predicted not to reach the design life of 15 years. Abstrak. Conveyor merupakan alat angkut yang digunakan di industri pertambangan untuk memindahkan bahan tambang. Struktur conveyor terbuat dari baja yang rawan mengalami korosi sebagai akibat pengaruh lingkungannya yang dapat menyebabkan pengurangan ketebalan dan mengurangi sisa umur pakai struktur conveyor. Penelitian ini dilakukan untuk mengetahui jenis korosi, metode mengendalian korosi, laju korosi, dan Remaining Service Life struktur conveyor. Metodologi yang digunakan dalam penelitian ini adalah pengukuran pengurangan ketebalan. Struktur conveyor memiliki panjang 96 meter yang terdiri dari 3 segmen dengan 25 test point. Pengukuran dilakukan dengan menggunakan Smart Sensor Ultrasonic Thickness Gauge TT 130. Output yang di dapat adalah nilai pengurangan ketebalan yang digunakan untuk menentukan Laju Korosi dan Sisa Umur Pakai. Kondisi lingkungan daerah penelitian tahun 2015-2020 memiliki curah hujan rata-rata 218,32 mm/tahun, kelembapan relatif rata-rata 81,37% dan suhu rata-rata 25,920C. Jenis korosi yang terjadi pada struktur conveyor adalah korosi merata. Metode pengendalian korosi yang digunakan yaitu metode coating dengan sistem three layers. Metode coating untuk primer coating menggunakan Seaguard 5000, Intermediate coating menggunakan Sherglass FF, dan Top coating menggunakan Aliphatic Acrylic Modified Polyurethane. Laju korosi struktur conveyor berkisar antara 0,1842 - 0,310 mm/tahun dan berdasarkan ketahanan korosi relatif baja termasuk ke dalam kategori good. Umur pakai struktur conveyor yaitu 7 tahun dan sisa umur pakai berkisar 6,53 - 9,49 tahun, sehingga terdapat 11 test point atau 44% test point yang diprediksi tidak dapat mencapai umur desain yaitu 15 tahun.